Eigenmeasures and stochastic diagonalization of bilinear maps - ERDOĞAN, EZGİ (WILEY, 2021)
A new stochastic approach is presented to understand general spectral type problems for (not necessarily linear) functions between topological spaces. In order to show its potential applications, we construct the theory for the case of bilinear forms acting in couples of a Banach space and its dual. Our method consists of using integral representations of bilinear maps that satisfy particular domination properties, which is shown to be equivalent to having a certain spectral structure. Thus, we develop a measure-based technique for the characterization of bilinear operators having a spectral representation, introducing the notion of eigenmeasure, which will become the central tool of our formalism. Specific applications are provided for operators between finite and infinite dimensional linear spaces.
Keywords: Banach space; eigenmeasure; eigenvalue; multilinear operators; nonlinear spectral theory